(untitled) (REMUNOM, 2023)
It is notorious that we talk about how the press has great influence today. With the great revolutions that erupted after the 18th century with the Industrial Revolution, which with each passing day, the ability to access mass information has become common. We currently have several favorable mechanisms within the judiciary, mainly the capacity for news, and to follow the facts that occur daily. However, we are dealing with a double-edged sword, the purpose of which is to demonstrate how these mechanisms for accessing information through the means of social communications can negatively contribute to criminal procedural practice, which may involve interventions in decision.